Estruturas de governança e recursos : geração e apropriação de valor no segmento produtor na microrregião de Goioerê/Paraná - Brasil, Sandra Aparecida (2015)
The Microregion of Goioerê, Parana State, stands out in the state scenario because of the volume of production provided by agricultural activities. Concomitant to this, this territorial crop constitutes one of the smallest microregions in the state and has shown reduction in the number of farms and an increase in the price of agricultural land. Due to this context, this study was conducted in order to understand how the value of ownership, generated through features, is influenced by governance structures used by agents that make up the rural production segment, located in the Microregion Goioerê, in the state of Parana. To this end, assumptions of the Theory of Economics of Transaction Costs were used in the context of the New Institutional Economics, considering transaction attributes and behavioral assumptions to the negotiations. Concurrently were assumptions of the theoretical approach called Resource-Based View, considering attributes and conditions of the available resources and make them a source of value creation. As methodological procedures, research, presenting qualitative and descriptive, it was conducted through semi-structured interviews with thirty agricultural producers who live and work in municipalities that comprise the studied microregion. The municipalities are: Altamira do Paraná, Boa Esperança, Campina da Lagoa, Goioerê, Janiópolis, Juranda, Moreira Sales, Nova Cantu, Rancho Alegre D'Oeste, Quarto Centenário and Ubiratã. Data analysis was designed considering the transactions between agents, attributes and dimensions present in them, and the resources available, their attributes and condition, outlining it from the following types of production: pultry slaughter, grains, dairy farming and hortifrutigranjeiros and agroindustrial products. The collected data were analyzed, considering the categories of analysis included in the purpose of the study, which were governance structures, resources, value creation, value appropriation and efficiency. As a result, it was identified that the main resources available to farmers are the fertile soil, favorable climate, management used and cooperative relations between producers. These resources are presented valuable and allow producers to generate income. Governance activities as integration structures have been identified as the production of seeds and seedlings and hybrid through formal and informal also contractual relationships. But mostly, governance structures were identified through the market, where producers have opted for greater encouragement and less control negotiations. Analyzing the context studied with producers in specific, and next to more broadly micro, it was noticed that heterogeneous and valuable resources enable the generation of value, enabling competitive advantage of reach. But to sustain competitive advantage the resources need to present other attributes and conditions, which prevent competitors to imitate them or replace them, which does not occur. The superiority condition of support in terms of volume of production presented by the micro-region is maintained in isolation mechanisms arising from Ricardian rents generated and path dependence in rural activities. Since the ownership of the generated value is influenced by governance structures. The governance structures, on the other hand, also contributing to generation of value to the extent that allow transaction costs are reduced.